(untitled) (Ameghiniana, 2013)
The knowledge of two Nothrotheriinae found in Uruguayan mio-pliocene deposits (Raigón Fm.) is enlarged by means of: 1) extension of Pronothrotherium Amegh., 1907 and P. mirabilis (Kragl., 1925) skull descriptions. 2) on the basis of this finding and precedent data, argumentation is provided for the incIusion of the type specimen of Senetia under synonymy with Pronothrotherium. 3) description of Pronothrotherium figueirasi n. sp. and a tentative proposal for a Montehermosan s. str. biochronologicaI distribution for that.